Fotografije na osebnih spletnih straneh kot možen vir antropološkega raziskovanja - Moličnik, Vesna (Traditiones (Ljubljana), 2001)
Most self-representations that include a photograph originate in the form of home pages on the internet. The paper looks at different ways by people who, by making use of this new medium, wish to convey something by enclosing photographs
Keywords: ethnology; etnologija; anthropology; antropologija; vizualne raziskave